Women Owning Land - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
WOMEN OWNING LANDThe issue of land tenure ? also addressed in Spore 75 ? is crucial to agricultural productivity. In certain circumstances the issue becomes critical, as in the case of societies which have lost much of their male population through...